A description of drug use among adolescents in Slovakia in different age and gender groups - Vavrová, Marta; Rojková, Zuzana (Technium Social Sciences Journal, 2020)
The paper describes the drug-using behaviour among young people (12-19 y.) within two age groups in Slovakia. The study aims to describe the prevalence of two different forms of drug-use (experimentation and use within the last 30 days) of legal and illegal substances: alcohol, nicotine (cigarettes), marijuana, and other illegal drugs. A descriptive analysis was applied to two age and gender groups. The research sample was made up of 2489 pupils in primary and secondary schools (various types) from different regions within Slovakia. One set was made up of 39.1% (N = 974) boys and 61.3% (N = 1515) girls aged 12-19 years which was divided into two age groups: group “14” (14 to 15 years, N = 923) and group “16” (16 and older, N = 1566). The SAHA method was used for data collection (Social and Health Assessment, Weissberg et al., 1991; a Slovak version by Rojková, 2017). Gender differences were tested statistically, and some differences were identified. The results are discussed in the context of European and national surveys that are available and a decrease in experimentation with marijuana and smoking was found.